2007
DOI: 10.1590/s0100-84042007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative propagation strategies of four rupestrian species of Leiothrix (Eriocaulaceae)

Abstract: -(Vegetative propagation strategies of four rupestrian species of Leiothrix (Eriocaulaceae)). Leiothrix is endemic of South America and includes 37 species, 25 of which occur in the state of Minas Gerais. Nineteen of those occur in the "Serra do Cipó", a mountain chain, located in the southern portion of the Espinhaço mountain range. This study examines vegetative propagation strategies of four species of Leiothrix, endemic to the Minas Gerais portion of the Espinhaço mountain range. For each species we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 15 publications
0
20
0
7
Order By: Relevance
“…Leiothrix spiralis and L. vivipara are both characterized by having a small body size in relation to other Leiothrix species (Coelho et al, 2007), early reproduction and rapid population increase. All these attributes can be associated with temporary and unpredictable habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leiothrix spiralis and L. vivipara are both characterized by having a small body size in relation to other Leiothrix species (Coelho et al, 2007), early reproduction and rapid population increase. All these attributes can be associated with temporary and unpredictable habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This may represent an attempt of early reproduction since Coelho et al (2007) found that the average diameter for these species are 3.7±0.3 cm and 2,5±0.1 cm. According to Hall and Willis (2006) and Franks et al (2007) the selection may favor early flowering in habitats where water availability decreases over the growing season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benites et al 2007, Ribeiro et al 2007). However, most mountain biodiversity research in Brazil is concentrated in elevations within the "cerrado" biome ("campos rupestres"; e.g., Coelho et al 2007, Figueira & Del Sarto 2007, Medina & Fernandes 2007, Velten & Garcia 2007, and in the "campos de altitude" of the Atlantic Rainforest biome (Martinelli 1996, Porembski et al 1998, Safford 1999, Safford & Martinelli 2000, Caiafa & Silva 2007, Ribeiro et al 2007). This pattern repeats itself in the present special issue: none of the studies published here are set in the Brazilian Amazon, and most concentrate within the "cerrado" and the Atlantic forest biomes.…”
Section: Mexico Guatemalamentioning
confidence: 99%
“…Campos de altitude e campos rupestres apresentam alta riqueza de espécies em escala local e regional, numerosos relictos e endemismos (Giulietti & Pirani 1988, Martinelli 1996, Safford 1999a, b, Rapini et al 2008, incluindo endemismos restritos ou microendemismos, em que são conhecidas apenas populações reduzidas que ocorrem em pequenas áreas com determinadas peculiaridades microambientais (Martinelli 1996, Ribeiro & Fernandes 2000, Coelho et al 2007, Rapini et al 2008. Valores precisos sobre a riqueza de espécies em campos rupestres e campos de altitude como um todo ainda não são disponíveis, mas para exemplo da magnitude dessa biodiversidade, se destaca o fato que das 13708 espécies de angiospermas listadas para o Domínio Mata Atlântica, cerca de ¼ (3592) ocorrem em formações campestres e 918 dessas são endêmicas desse domínio (Stehmann et al 2009), em que pese a pequena proporção de área de ocorrência dos campos em relação às formações florestais.…”
Section: Introductionunclassified